2001
DOI: 10.1093/jmicro/50.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Localization of receptor activator of NFkappaB ligand, RANKL, in periodontal tissues during experimental movement of rat molars

Abstract: The receptor activator of NFkappaB ligand, RANKL, is one of the key regulatory molecules in osteoclast formation and function. We examined RANKL localization in the periodontal tissues during experimental movement of rat molars. To produce orthodontic force, an elastic band was inserted between the upper first and second molars for 4 days, and the dissected maxillae were subjected to light and electron microscopic immunocytochemical examination for RANKL. Expression of RANKL protein was detected in osteoblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 0 publications
6
37
1
4
Order By: Relevance
“…We previously localized RANKL expression in PDL fibroblasts and osteoblasts on the compressed side of the PDL (Shiotani et al, 2001). Because cell-to-cell interaction between osteoblasts/stromal cells and osteoclast precursors is essential for osteoclast formation Matsuzaki et al, 1998;Tsukii et al, 1998), our observation suggests that these osteoblasts/stromal cells and fibroblasts in PDL are involved in supporting osteoclast differentiation during tooth movement.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We previously localized RANKL expression in PDL fibroblasts and osteoblasts on the compressed side of the PDL (Shiotani et al, 2001). Because cell-to-cell interaction between osteoblasts/stromal cells and osteoclast precursors is essential for osteoclast formation Matsuzaki et al, 1998;Tsukii et al, 1998), our observation suggests that these osteoblasts/stromal cells and fibroblasts in PDL are involved in supporting osteoclast differentiation during tooth movement.…”
Section: Discussionmentioning
confidence: 73%
“…We recently localized RANKL expression in PDL tissue during orthodontic tooth movement (Shiotani et al, 2001). However, the involvement of RANKL and OPG in PDL tissue during orthodontic tooth movement has not yet been examined.…”
mentioning
confidence: 99%
“…Indeed, it has been shown that application of orthodontic forces results in the expression of RANKL protein in osteoblasts, osteocytes, fibroblasts, and osteoclasts [42]. In our studies, we utilized the knowledge of the basic biologic mechanisms of osteoclastogenesis and the important role played by the OPG-RANKL axis in osteoclast function to test the hypothesis that OPG participates in mechano-modulation of osteolysis to diminish orthodontic tooth movement and could therefore serve as a biologic mediator for enhancing orthodontic anchorage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent immunocytochemical study reported that RANKL/RANK and M-CSF/c-fms were also observed in osteoblasts, osteocytes, fibroblasts, osteoclasts, and odontoclasts during the application of orthodontic forces. 16,17 Furthermore, recent studies have recognized the role of inflammatory cytokines such as IL-8 in transmitting signals for osteoclastogenesis. 18 It is reported that RANKL/RANK, M-CSF/c-fms, and IL-8 are expressed in root resorption lacunae around rat molar by heavy orthodontic force.…”
Section: Discussionmentioning
confidence: 99%